Análisis de la viabilidad poblacional de Rhea pennata en Perú - Maldonado Chambi, Willy (2024)
In this work, a population viability analysis (PVA) is conducted on the population of Rhea pennata, a bird categorized as Critically Endangered (CR), with an estimated population size of 350 individuals in Peru. The data were analyzed using VORTEX 9.6 software, and eight scenarios and combinations were modeled to determine the annual population growth rate under the influence of anthropogenic, demographic, environmental, and genetic factors. The results indicate that the Rhea pennata population is not viable, with a negative population growth rate (r= −0.11), meaning the population decreases by 11% per year. A combined effect of anthropogenic factors, such as egg collection, genetic factors like inbreeding, and environmental factors such as intense snowfalls, further reduces the growth rate (r= −0.18). In this scenario, the probability of extinction occurs in approximately 50 years. The effect of inbreeding in an adult population of 50 individuals in a fragmented habitat would lead to extinction in approximately 25 to 30 years. The only scenario where the population is viable in the long term involves repopulation, requiring the release of 38 population groups over a period of 15 years in an area of approximately 27000 km2, which must be under some conservation measure, such as protected natural areas or other area-based conservation measures.